What ails India’s free trade agreements? - Pohit, Sanjib; Pal, Barun Deb (Indian Express Group, 2020)
Lately, India’s trade policy seem to lack a vision. After actively pursuing it for over a decade, India decided against joining RCEP at the eleventh hour. The official version is that India runs a large trade deficit with RCEP countries, and was expecting specific protection for its industry and farmers from a surge in imports, especially from China. Since that did not materialise, the government of India does not foresee any gain from joining RCEP. Moreover, it may hamper India’s Make in India programme. In hindsight, this may be an afterthought of signing several free trade agreements (FTAs) with Far East countries/blocs (Korea, ASEAN, Japan) in the past (under UPA), the gains of which are not clearly visible. In fact, the official view is that poor negotiations of FTAs under previous governments have harmed Indian industry, and led to a distorted trade balance. While the outcome variable (distorted trade balance) is shown by statistics, the factor behind this trend needs in-depth introspection. The question is whether these FTAs escalate the non-tariff measures (NTMs), leading to higher trade deficit. This is indeed a possibility if policymakers didn’t pay enough attention to creating a complementary ecosystem, in terms of trade facilitation measures for efficient functioning of the trade regime, at the time of signing of FTA.